First demonstration of full ELM suppression in low input torque plasmas to support ITER research plan using n = 4 RMP in EAST. (12th October 2021) - Sun, Y.; Ma, Q.; Jia, M.; Gu, S.; Loarte, A.; Liang, Y.; Liu, Y.Q.; Paz-Soldan, C.A.; Wu, X.M.; Xie, P.C.; Ye, C.; Wang, H.H.; et al.
Abstract: Full suppression of type-I edge localized modes (ELMs) using n = 4 resonant magnetic perturbations (RMPs) as planned for ITER has been demonstrated for the first time ( n is the toroidal mode number of the applied RMP). This is achieved in EAST plasmas with low input torque and tungsten divertor, and the target plasma for these experiments in EAST is chosen to be relevant to the ITER Q = 10 operational scenario, thus also addressing significant scenario issues for ITER. In these experiments the lowest neutral beam injection (NBI) input torque is around T NBI ∼ 0.44 Nm, which extrapolates to around 14 Nm in ITER (compared to a total torque input of 35 Nm when 33 MW of NBI are used for heating). The q 95 is around 3.6 and normalized plasma beta β N ∼ 1.5–1.8, similar to that in the ITER Q = 10 scenario. Suppression windows in both q 95 and plasma density are observed; in addition, lower plasma rotation is found to be favourabe to access ELM suppression. ELM suppression is maintained with line averaged density up to 60% n GW (Greenwald density limit) by feedforward gas fuelling after suppression is achieved. It is interesting to note that in addition to an upper density, a low density threshold for ELM suppression of 40% n GW is also observed. In these conditions energy confinement does not significantly drop (<10%) during ELM suppression when compared to the ELM y H-mode conditions, which is much better than previous results using low n ( n = 1 and 2) RMPs in higher q 95 regimes. In addition, the core plasma tungsten concentration is clearly reduced during ELM suppression demonstrating an effective impurity exhaust. MHD response modelling using the MARS-F code shows that edge magnetic field stochasticity has a peak at q 95 ∼ 3.65 for the odd parity configuration, which is consistent to the observed suppression window around 3.6–3.75. These results expand the physical understanding of ELM suppression and demonstrate the effectiveness of n = 4 RMPs for reliable control ELMs in future ITER high Q plasma scenarios with minimum detrimental effects on plasma confinement.